Knowledge domain and emerging trends in brachytherapy: A scientometric analysis. Issue Volume 6:Issues 3(2022) (14th September 2022) - Ghazbani, Arash; Abdolahi, Mohammad; Mansourzadeh, Mohammad Javad; BasirianJahromi, Reza; Behzadipour, Sina; Mohseni Azad, Anali; Talebzadeh, Bardia; Khosravi, Abdolrasoul; Hamidi, Ali
Abstract: Objective: Assessing the current scientific situation helps to recognize the gaps and strengths of brachytherapy research projects. This research project was conducted to assess the knowledge domain and emerging trends in brachytherapy through a scientometric perspective. Methods: For the present research, the Web of Science database was considered as the data source. Integrated data was transferred to Bibliometrix R Package V3.1. In this study, the scientometric approach was performed by CiteSpace 5.8.R3 to draw the trends and signify issues in the research area. Eventually, scientometric indicators were evaluated at the level of authors, documents, journals, organizations, and countries. Results: A total of 31, 362 documents from 64, 740 Independent researchers were retrieved. The United States, Germany, and Canada were the most active countries in brachytherapy‐related research projects. In the present study, Luc Beaulieu, Christine Kirisits, and Ronald Nath were identified as the most influential authors. Eventually, keywords clusters were constructed by using the method of co‐citation analysis. In this case, the main clusters were cervical cancer and prostate cancer. Conclusion: Assessing the scientific trends in brachytherapy indicated that new insights have been gained into this cancer treatment technique. In this case, development of computer applications and artificial intelligence alongside deep learning utilization provides new horizons for oncology and radiotherapy researchers. Abstract : For this, the Web of Science database was considered as the data source. Integrated data were transferred to Bibliometrix R Package V3.1 and the scientometric approach was performed by CiteSpace 5.8.R3 to draw the trends and signify issues in the research area. Finally, scientometric indicators were evaluated at the level of authors, documents, journals, organizations, and countries. A total of 31, 362 documents were retrieved. The United States, Germany, and Canada were the most active countries in brachytherapy‐related research projects. Luc Beaulieu, Christine Kirisits, and Ronald Nath were identified as the most influential authors. Keywords clusters were constructed using the method of co‐citation analysis and the main clusters were cervical cancer and prostate cancer. Evaluating scientific productions in the field of brachytherapy indicated that new insights have been gained into this cancer treatment technique. The development of computer applications and artificial intelligence alongside deep learning utilization are new horizons for oncology and radiotherapy researchers.